Digital platform for rice yield simulation under current and future climate conditions - Donou, Cedarta; Dossou-Yovo, E. R (2024)
A digital platform for rice yield simulation is essential for assessing the impact of climate change on rice production and guiding adaptation strategies. Using data from 17,647 fields across 12 West African countries, the tool integrates climate, soil, and agronomic variables, achieving over 75% accuracy in yield prediction. It incorporates future climate scenarios, enabling the assessment of climate change impacts and the identification of appropriate adaptation technologies. To maximize the impact of the digital platform for rice yield simulation, challenges such as data limitations, model assumptions, and accessibility issues must be addressed by strengthening data collection, refining model calibration, and improving user engagement. Key recommendations include enhancing data integration, improving model accuracy, increasing accessibility, providing training, fostering stakeholder collaboration, and incorporating climate risk management to support climate resilience and sustainable rice production in West Africa.